Antibacterial dihydrobenzopyran and xanthone derivatives from Garcinia cowa stem barks - Siridechakorn I. (Elsevier, 2015)
Two new compounds, garciniacowol (1) and garciniacowone (2) along with 15 known compounds were isolated from the stem barks of Garcinia cowa. Their structures were determined by intensive spectroscopic methods. The structure of 1 was a symmetrical dimeric dihydrobenzopyran derivative, whereas the framework of 2 was a triprenyl caged-xanthone precursor. The antibacterial activities against Escherichia coli TISTR 780, Salmonella typhimurium TISTR 292, Staphylococcus aureus TISTR 1466, and methicillin-resistant S. aureus (MRSA) SK1 of the isolated compounds were also evaluated. Compounds 2 and 9 exhibited good antibacterial activity against MRSA SK1 with the same minimum inhibitory concentration (MIC) value of 2 μg/mL. Moreover, compound 2 also showed good antibacterial activity against S. aureus with an MIC value of 2 μg/mL. © 2012 Elsevier B.V.